2016
DOI: 10.1302/0301-620x.98b8.37469
|View full text |Cite
|
Sign up to set email alerts
|

Are radiographic measurements of the displacement of a distal radial fracture reliable and reproducible?

Abstract: Radiographic assessment of radial angle, radial inclination and dorsal/palmar tilt is a reliable method of determining the degree of displacement of a fracture of the distal radius. Cite this article: Bone Joint J 2016;98-B:1069-73.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
3
18
0
2
Order By: Relevance
“…Most previous studies on measurements performed on native radiographs have shown moderate or good reliability concerning extra-articular fractures, but the reliability for evaluating articular surface incongruence is poor (Kreder et al., 1996; Stirling et al., 2016; Suojärvi et al., 2015; Watson et al., 2016). A thorough review on the radiographic parameters of distal radius fractures showed marked variability in the actual description of performing the measurements (Lalone et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies on measurements performed on native radiographs have shown moderate or good reliability concerning extra-articular fractures, but the reliability for evaluating articular surface incongruence is poor (Kreder et al., 1996; Stirling et al., 2016; Suojärvi et al., 2015; Watson et al., 2016). A thorough review on the radiographic parameters of distal radius fractures showed marked variability in the actual description of performing the measurements (Lalone et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
“…If the diagnostic test (reading the radiograph) is not necessarily accurate, then it follows that the ensuing clinical action may be equally inaccurate. Disagreement in radiographic interpretation is well documented in the medical literature and thus is not a unique finding related to dentistry (Angoulvant, et al, ; Rubenfeld, Caldwell, Granton, Hudson, & Matthay, ; Stirling, Jeffery, Johnson, & Dias, ).…”
Section: Discussionmentioning
confidence: 99%
“…A senior radiologist (H.B. ), who was blinded to patient outcome, conducted all radiographic measurements with use of a standardized protocol 30 , 31 . Range of motion was measured with a goniometer.…”
Section: Methodsmentioning
confidence: 99%